Low Plasma Volume in Normotensive Formerly Preeclamptic Women Predisposes to Hypertension. Issue 5 (November 2015) - Scholten, Ralph R.; Lotgering, Fred K.; Hopman, Maria T.; Van Dijk, Arie; Van de Vlugt, Maureen; Janssen, Mirian C.H.; Spaanderman, Marc E.A.
Abstract : Formerly preeclamptic women are at risk for cardiovascular disease. Low plasma volume may reflect latent hypertension and potentially links preeclampsia with chronic cardiovascular disease. We hypothesized that low plasma volume in normotensive formerly preeclamptic women predisposes to hypertension. We longitudinally studied n=104 formerly preeclamptic women in whom plasma volume was measured 3 to 30 months after the preeclamptic pregnancy. Cardiovascular variables were assessed at 2 points in time (3–30 months postpartum and 2–5 years thereafter). Study population was divided into low plasma volume (⩽1373 mL/m 2 ) and normal plasma volume (>1373 mL/m 2 ). Primary end point was hypertension at the second visit: defined as ≥140 mm Hg systolic or ≥90 mm Hg diastolic. Secondary outcome of this study was change in traditional cardiovascular risk profile between visits. Variables correlating univariately with change in blood pressure between visits were introduced in regression analysis. Eighteen of 104 (17%) formerly preeclamptic women who were normotensive at first visit had hypertension at second evaluation 2 to 5 years later. Hypertension developed more often in women with low plasma volume (10/35 [29%]) than in women with normal plasma volume (8/69 [12%]; odds ratio, 3.2; 95% confidence interval, 1.4–8.6). After adjustments, relationship between plasma volume status and subsequent hypertension persisted (adjusted odds ratio, 3.0; 95% confidence interval, 1.1–8.5). Mean arterial pressure at second visit correlated inverse linearly with plasma volume ( r =−0.49; P <0.01). Initially normotensive formerly preeclamptic women have 17% chance to develop hypertension within 5 years. Women with low plasma volume have higher chance to develop hypertension than women with normal plasma volume. Clinically, follow-up of blood pressure seems warranted in women with history of preeclampsia, even when initially normotensive.